Six Sigma as a Method for Controlling and Improving the Quality of Bed Series Products - Untoro, Octa Bimansyah; Iftadi, Irwan (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2020)
The research was conducted at PT. XYZ where there were defect problems in bed series products so that additional time is needed to repair a product. One way to make improvements and improve quality in a production process is the Six Sigma method with the stages of DMAIC. The results of the calculated average of DPMO values and Sigma Level have the result 58558.56 and 3.07 which are still not good because still far from 6 sigma. After that analyzing the root causes of defect product problems, then the priority problem is carried out using (RPN) where the highest value is at the assembly work station because the material that has been used up in the warehouse has an RPN of 405 so that it becomes a top priority for repairs. With the standardization and documentation, proposed improvements that have been given then the possible defects of Electric Lovina Bed 3 Motor will be reduced.